Labor justice across the Americas - Fink, Leon, 1948-; Palacio, Juan Manuel (Working class in American history., 2018)
Opinions of specialized labor courts differ, but labor justice undoubtedly represented a decisive moment in worker 's history. When and how did these courts take shape? Why did their originators consider them necessary? Leon Fink and Juan Manuel Palacio present essays that address these essential questions. Ranging from Canada and the United States to Chile and Argentina, the authors search for common factors in the appearance of labor courts while recognizing the specific character of the creative process in each nation. Their transnational and comparative approach advances a global perspective on the various mechanisms for regulating industrial relations and resolving labor conflicts. The result is the first country-by-country study of its kind, one that addresses a defining shift in law in the first half of the twentieth century.